Mediation for the solution of urban problems: The search for environmental quality for present and future generations by applying governance processes. - Garcez, Gabriela; Cardoso, Simone (International Planning History Society Proceedings, 2016)
This paper aims to demonstrate the importance of Law 13.140/2015, which provides mediation as a mean of settling disputes within public administration for the materialization and execution of intergenerational solidarity. In this sense, this paper is not just a study of a specific case, but it has the intention to highlight the importance of this regulation for the solution of urban conflicts. This law solidifies a Brazilian public policy of consensual methods for conflict resolution, which began with the Constitutional amendment nº. 45/2004, considered the framework for judicial reform in pursuit of efficiency. After, the National Judicial Council issued the Resolution nº.125/2010, establishing mediation as an appropriate tool for conflict resolution. The historical course for consolidation of this trend was the enactment of Law 13.140/2015, with importance closely related of management, prevention and resolution of urban environmental conflicts. These conflicts have materialized around the use and occupation of urban land, as in most large Brazilian centers, according Pioli and Rossin (2006), accelerated urbanization, coupled with the imbalance of income distribution, generated towns with peripheral human settlements, that reflect and perpetuate inequalities, promote social exclusion, environmental degradation and exposes the inability of State to intervention in the implementation of effective public policies for environmental protection, social inclusion and conflict resolution. For this reason, it is necessary to have a effective cooperation between the various State levels for convergence between social policies and conflict resolution. Moreover, it is timely an analysis and interpretation of Mediation Act, to determine whether it may contribute to resilience of urban system, in the sense that the resilient societies are also those that have the capacity to mediate the differences with cordiality and tolerance. Because, sustainable development based on resilience requires governance in the pursuit of social peace. Hence, the need for participatory actions of those involved in the conflict, which can be achieved through governance by public-private cooperation in solving social problems and new forms of multilevel policy. Following this dynamic, the implementation of mediation can be seen as an important tool for urban environmental governance arrangements, which will manage, prevent and resolve conflicts around the urban areas in search of intergenerational solidarity, because this new form of conflict resolution is an undeniable part of the mechanisms for the implementation of a effective governance, as it allows the participation and dialogue between different actors, seeking a beneficial solution and adopting a peaceful model based on cooperation. In this line of reasoning, this paper discusses, at first, the governance, evaluating its concept and importance. Then, it analyzes the role of new forms of conflict resolution, focusing on mediation for solving urban problems, indicating the historical development of mediation in the Brazilian legislation. Finally, it discusses the possibility of using this mechanism for the defense and protection of urban environment, aiming the maintenance of environmental quality for present and future generations, in respect to the principle of intergenerational solidarity, adopted by the Brazilian Federal Constitution of 1988.